DETEKSI CEPAT BAKTERI Escherichia coli DALAM SAMPEL AIR DENGAN METODE POLYMERASE CHAIN REACTION MENGGUNAKAN PRIMER 16E1 DAN 16E2 - Radji, Maksum; Puspaningrum, Anglia; Sumiati, Atiek (UI Scholars Hub, 2010)
Rapid Detection of Escherichia coli in Water Samples by Polymerase Chain Reaction Using 16E1 and 16E2 Primers. The detection of Escherichia coli in various water samples by Polymerase Chain Reaction method using 16E1 and 16E2 primers has been carried out. It was found that four out of ten samples were detected Escherichia coli and revealed the presence of the amplified product of the size 584 base pairs. Confirmation test of PCR result was also done using the conventional culturing method. The results of this study showed that the PCR assay was specific and faster than the conventional culturing method for detection of Escherichia coli.